PENERAPAN RAPID APPLICATION DEVELOPMENT PADA PERANCANGAN SISTEM INFORMASI PEMBELIAN BARANG (SI BERANG) - Helling, Lydia Salvina (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2021)
Kranggan Jaya is one form of a company engaged in the sale and purchase of building goods where the buying and ordering process that occurs so far is still manual. Recording and calculations in transactions that require accuracy, often get into trouble to the detriment of the store. This is what underlies the need for a process that runs automatically with the use of information systems. The construction of SIBeRang for TB. Kranggan Jaya is urgently needed to answer the challenges faced in business competition in businesses related to building shops. The Rapid Application Development method is used in software development and data collection through direct observation of the purchasing process, ordering goods until the goods ordered are received by the warehouse. In this study, in addition to interviews with warehouse employees and purchases. SIBeRang finally overcome this problem so that the existing data becomes accurate and can be accounted for. In addition to TB. Kranggan Jaya, suppliers benefit from this information system by making it easy to obtain data on ordering goods without having to come to take documents to the building shop.